Use of inhaled corticosteroids in preschool children and variability among pediatricians: a real-world analysis before and during the SARS-CoV-2 pandemic - Michela Alagna; Antonio Clavenna; Laura Reali; Adele Lallo; Danilo Fusco; Marina Davoli; Mirko Di Martino (BMC, 2023)
Abstract Background In Italy, inhaled corticosteroids (ICSs) are inappropriately prescribed to provide relief in URTI symptoms. Extreme variation in ICS prescribing has been described at regional and sub-regional level. During 2020, extraordinary containment measures were implemented in attempt to halt Coronavirus, such as social distancing, lockdown, and the use of mask. Our objectives were to evaluate the indirect impact of the SARS-CoV-2 pandemic on prescribing patterns of ICSs in preschool children and to estimate the prescribing variability among pediatricians before and during the pandemic. Methods In this real-world study, we enrolled all children residing in the Lazio region (Italy), aged 5 years or less during the period 2017-2020. The main outcome measures were the annual ICS prescription prevalence, and the variability in ICS prescribing, for each study year. Variability was expressed as Median Odds Ratios (MORs). If the MOR is 1.00, there is no variation between clusters (e.g., pediatricians). If there is considerable between-cluster variation, the MOR will be large. Results The study population consisted of 210,996 children, cared by 738 pediatricians located in the 46 local health districts (LHDs). Before the pandemic, the percentage of children exposed to ICS was almost stable, ranging from 27.3 to 29.1%. During the SARS-CoV-2 pandemic, the ICS prescription prevalence dropped to 17.0% (p < 0.001). In each study year, a relevant (p < 0.001) variability was detected among both LHDs and pediatricians working in the same LHD. However, the variability among individual pediatricians was always higher. In 2020, the MOR among pediatricians was 1.77 (95% CI: 1.71-1.83) whereas the MOR among LHDs was 1.29 (1.21-1.40). Furthermore, MORs remained stable over time, and no differences were detected in ICS prescription variability before and after pandemic outbreak. Conclusions If on one hand the SARS-CoV-2 pandemic indirectly caused the reduction in ICS prescriptions, on the other the variability in ICS prescribing habits among both LHDs and pediatricians remained stable over the whole study time span (2017-2020), showing no differences between pre- pandemic and pandemic periods. The intra-regional drug prescribing variability underlines the lack of shared guidelines for appropriate ICS therapy in preschool children, and raises equity issues in access to optimal care.